Increased Number of Circulating CD8/CD26 T Cells in the Blood of Duchenne Muscular Dystrophy Patients Is Associated with Augmented Binding of Adenosine Deaminase and Higher Muscular Strength Scores - Jonathan H. Soslow; Larry W. Markham; Larry W. Markham; W. Bryan Burnette; Cristi L. Galindo; Igor Feoktistov; Frank J. Raucci; Bruce M. Damon; Douglas B. Sawyer; Douglas B. Sawyer; Sergey Ryzhov (Frontiers Media S.A., 2017)
Duchenne muscular dystrophy (DMD) is an X-linked disorder that leads to cardiac and skeletal myopathy. The complex immune activation in boys with DMD is incompletely understood. To better understand the contribution of the immune system into the progression of DMD, we performed a systematic characterization of immune cell subpopulations obtained from peripheral blood of DMD subjects and control donors. We found that the number of CD8 cells expressing CD26 (also known as adenosine deaminase complexing protein 2) was increased in DMD subjects compared to control. No differences, however, were found in the levels of circulating factors associated with pro-inflammatory activation of CD8/CD26 cells, such as tumor necrosis factor-α (TNFα), granzyme B, and interferon-γ (IFNγ). The number of CD8/CD26 cells correlated directly with quantitative muscle testing (QMT) in DMD subjects. Since CD26 mediates binding of adenosine deaminase (ADA) to the T cell surface, we tested ADA-binding capacity of CD8/CD26 cells and the activity of bound ADA. We found that mononuclear cells (MNC) obtained from DMD subjects with an increased number of CD8/CD26 T cells had a greater capacity to bind ADA. In addition, these MNC demonstrated increased hydrolytic deamination of adenosine to inosine. Altogether, our data demonstrated that (1) an increased number of circulating CD8/CD26 T cells is associated with preservation of muscle strength in DMD subjects, and (2) CD8/CD26 T cells from DMD subjects mediated degradation of adenosine by adenosine deaminase. These results support a role for T cells in slowing the decline in skeletal muscle function, and a need for further investigation into contribution of CD8/CD26 T cells in the regulation of chronic inflammation associated with DMD.